The Concept of Safe Third Country with Special Regard to the Greek Safe Third Country Declaration - Đukić, Dalibor (Migration and Central Europe: Challenges and Legal Responses, 2024)
This study explores the “safe third country” (STC) concept as outlined in the Dublin III Regulation of the European Union, focusing specifically on the Greek list of designated STCs. The concept of STC is viewed as a strategic tool used by developed countries to address challenges such as “asylum shopping” and “orbit” situations. However, there are significant concerns about its compliance with international law, especially the 1951 Refugee Convention. In 2021, Greece issued a Joint Ministerial Decision designating Türkiye as an STC for certain nationals. This designation was later expanded to include Albania and northern Macedonia. Despite criticism, the Greek authorities continued to implement their decisions, resulting in many applications being deemed inadmissible and applicants being ordered to return to Türkiye, even though such readmissions have been suspended since 2020. The Greek Council of States affirmed that designating Türkiye as a STC met the requirements of the Revised Asylum Procedures Directive. To be considered an STC, countries should typically have stable political environments, effective legal systems, respect for human rights, and established asylum procedures. However, the present study highlights how the interpretation of STC rules varies significantly. The effectiveness of the STC principle hinges on the provision of effective protections for asylum seekers. Although the standard for effective protection may be ambiguous, if used effectively, the STC concept can enhance the efficiency of asylum procedures without compromising the rights of asylum seekers’ rights. The STC concept has the potential to improve the asylum process by reducing irregular migration and deterring human trafficking and smuggling. Nonetheless, a merit-based evaluation of individual applications, including asylum seeker’s circumstances and conditions in designated STC, remains crucial.Keywords: safe third country, safe country of origin, European safe third country, Greece, refugees, migration, national safe third country lists